Recent advances in smooth muscle tumors with PGR and PLAG1 gene fusions and myofibroblastic uterine neoplasms. Issue 3 (8th December 2020) - Chiang, Sarah
Abstract: Uterine epithelioid and myxoid leiomyosarcomas and inflammatory myofibroblastic tumors are rare mesenchymal neoplasms. Next‐generation sequencing recently detected novel PGR fusions in uterine epithelioid leiomyosarcomas that demonstrate characteristic rhabdoid and spindled morphology. PLAG1 gene fusions have also been identified in a subset of myxoid leiomyosarcomas and are associated with PLAG1 overexpression. ALK rearrangements underpin the vast majority of uterine inflammatory myofibroblastic tumors, which demonstrate morphologic, and immunohistochemical features similar to those of inflammatory myofibroblastic tumors elsewhere. This review summarizes the morphologic, immunophenotypic, and molecular genetic features of PGR fusion‐positive epithelioid leiomyosarcoma, PLAG1 fusion‐positive myxoid leiomyosarcoma, and inflammatory myofibroblastic tumors of the uterus.